High Gastrointestinal Colonization Rate of Vancomycin-Resistant Enterococci among Hospitalized Patients: Potential Source for Resistant Gene - Techilo Habtemariam Mengesha; Musa Mohammed Ali; Mulugeta Mengistu; Demissie Assegu Fenta (International Journal of Microbiology)
Background. Vancomycin-resistant Enterococci (VRE) is a global health problem and responsible for healthcare-associated infections (HAIs) in patients with prolonged hospital stay, severe underlying disease, and previous broad-spectrum antibiotic therapy. These bacteria can cross-resist and transfer drug-resistant genes to other potentially pathogenic bacteria. Therefore; this study was aimed to determine the gastrointestinal colonization rate of VRE, its antimicrobial susceptibility profile, and associated factors among hospitalized patients. Methods. Prospective cross-sectional study was conducted using stool samples from 223 patients admitted to different wards at Hawassa University Comprehensive Specialized Hospital, from April 1 to June 30, 2021. Patients admitted to the hospital for more than 48 hours for various medical conditions were included. Sociodemographic and clinical characteristics were collected using a structured questionnaire. Fecal specimens were cultured on Enterococci selective media. Enterococcus species were identified using their growth and mannitol fermentation properties. Vancomycin resistance was screened using both the Kirby–Bauer disk diffusion method and a vancomycin E-test strip. Data were entered and analyzed using SPSS version 25. Descriptive and logistic regressions were used to determine the frequency and association of factors with the VRE colonization rate. A p value of <0.05 was considered statistically significant. Results. A total of 223 fecal specimens were collected and processed, and 141 (63.2%) them were positive for Enterococci. The predominant species was E. faecalis 65 (46.1%) followed by E. faecium 76 (53.9%). In this study, the gastrointestinal colonization rate of VRE was 15 (6.7%) and all the species belong to E. faecium. Study participants who had no formal education (AOR = 4.26, 95% CI: 1.01, 18.06), hospitalized patients for >2 weeks (AOR = 4.10, 95% CI: 1.08, 15.57), and those who had a history of treatment with vancomycin (AOR = 4.77, 95% CI: 1.26, 18.09) were more likely to be colonized with vancomycin-resistant Enterococci. More than 95% of Enterococci isolates were susceptible to linezolid, whereas 70.2%, 63.1%, 56.7%, and 53.9% were resistant to tetracycline, erythromycin, penicillin, and ampicillin, respectively. Among the total Enterococci isolated, 141 (54.6%) were multidrug resistant. Conclusions. In our study, high proportion of vancomycin-resistant Enterococci was found. Previous exposure to antibiotics and hospital stay were significant factors for VRE gut colonization. The isolated Enterococci showed variable degrees of resistance to commonly prescribed antibiotics which leads to a worldwide problem multidrug resistance. Therefore, periodic surveillance on antimicrobial resistance pattern, adhering to rational use of antibiotics, and implementing infection prevention protocols may reduce colonization by VRE.